Bienvenidos A Bordo: From Task-Based Needs Analysis to Design: Spanish-Destination Flight Attendants - Keller, Shakira; Gilabert, Roger (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2023)
The aim of this task-based needs analysis is two-fold: firstly, to uncover the tasks performed by U.S.-based Spanish-language flight attendants and the associated language needs and, in doing so, to expand the breadth of task-based needs analysis (TBNA) through the application of multiple methods and sources (Long, 2005) and tackling the under-researched issue of transfer from TBNA to task design (Gilabert & Malica, 2021a; 2021b). A questionnaire-guided interview and online survey were used. Analysis of the extracted information illuminated the essential tasks and subtasks (Gilabert, 2005), including details regarding frequency, need for training, and language use. Findings suggest that each task and subtask requires varying amounts of Spanish, as well as knowledge of distinct linguistic dimensions. Triangulation of multiple sources and methods adds to the understanding of the tasks and language needs. Finally, suggestions as to how the outcome of this NA may transfer to task design are presented, hence extending the field of TBNA.